Anarchism and ecological epistemologies in transpacific speculative fiction - Kim, Anthony, author; Ishiwata, Eric, advisor; Sorensen, Leif, committee member; Souza, Caridad, committee member (Colorado State University. Libraries, 2018)
This thesis examines works of transnational speculative fiction from across the Pacific for anarchist themes and the influence of ecologically-based epistemologies. Texts examined in this thesis include films by South Korean director Bong Joon Ho and works by writers and other creatives of color based primarily in North America.